The multi metal-resistant bacterium Cupriavidus metallidurans CH34 affects growth and metal mobilization in Arabidopsis thaliana plants exposed to copper - Claudia Clavero-León (PeerJ, 2021)
Copper (Cu) is important for plant growth, but high concentrations can lead to detrimental effects such as primary root length inhibition, vegetative tissue chlorosis, and even plant death. The interaction between plant-soil microbiota and roots can potentially affect metal mobility and availability, and, therefore, overall plant metal concentration. Cupriavidus metallidurans CH34 is a multi metal-resistant bacterial model that alters metal mobility and bioavailability through ion pumping, metal complexation, and reduction processes. The interactions between strain CH34 and plants may affect the growth, metal uptake, and translocation of Arabidopsis thaliana plants that are exposed to or not exposed to Cu. In this study, we looked also at the specific gene expression changes in C. metallidurans when co-cultured with Cu-exposed A. thaliana. We found that A. thaliana’s rosette area, primary and secondary root growth, and dry weight were affected by strain CH34, and that beneficial or detrimental effects depended on Cu concentration. An increase in some plant growth parameters was observed at copper concentrations lower than 50 µM and significant detrimental effects were found at concentrations higher than 50 µM Cu. We also observed up to a 90% increase and 60% decrease in metal accumulation and mobilization in inoculated A. thaliana. In turn, copper-stressed A. thaliana altered C. metallidurans colonization, and cop genes that encoded copper resistance in strain CH34 were induced by the combination of A. thaliana and Cu. These results reveal the complexity of the plant-bacteria-metal triad and will contribute to our understanding of their applications in plant growth promotion, protection, and phytoremediation strategies.